Determinants of Success in Mathematics Student Teaching at the UP Integrated School - Sonza, Michelle S. (Alipato, A Journal of Basic Education; Vol 3 No 2 (2008), 2025)
Student teaching is a vital component of teacher education. The program gives student teachers the opportunity to learn the basic skills needed to become expert teachers, and provides them determinants of success in the teaching profession. In terms of mathematics student teaching, two of the determinants of success theorized were (1) the mode of entry into the UP College of Education (CoEd), whether as an original freshman of the college or as a "shiftee" from another college, and (2) performance in (a) content courses, (b) methods courses, and (c) test and measurement courses. Success in mathematics student teaching is ultimately measured through the final grade in EDUC 180, the student-teaching course. For the purposes of this study, Mathematics student teachers for two consecutive academic years, 2005-2006 and 2006-2007, were engaged.  The results of the study indicated that the mode of entry into the CoEd and the performance of the student teacher in all his/her content courses (grades in all the required courses in Mathematics) are determinants of success in student teaching. Moreover, the study revealed that the student teachers’ performance in student teaching is significantly correlated with their performance in their content and methods courses.